O impacto da invasão da braquiária (Urochloa sp.) na diversidade de formigas, no cerrado da estação ecológica de Santa Bárbara e Itirapina, sp. - Bandeira, João Pedro Ferreira de Pádua (Universidade Federal de São Carlos, 2021)
The invasion of African grasses is a problem in the cerrado. These exotic grasses competitively outperform native grasses and alter structural features of the habitat. One of these species, the brachiaria (Signal grass), has the ability to cause profound changes in the invaded environment, such as replacing native grasses and increasing plant biomass. Changes promoted by the brachiaria affect the insect fauna that inhabit the invaded areas, promoting changes in their populations and community composition, as well as in the ecological processes in which they participate. Our work aims to assess whether the brachiaria affects the cerrado ant communities. We compared the ant fauna in places invaded or not by brachiaria in fragments of cerrado in Itirapina and Águas de Santa Bárbara. Sampling transects were placed both in areas of native grasses and in areas invaded by the brachiaria. Pitfall traps were placed at each 20 m along the transect to sample the ants that forage on the soil surface. After sampling, we screened the samples and identified ants up to genus level. We made rarefaction curves, non-parametric tests (NMDS) and chi-square tests to compare species richness and similarity between treatments. We detected a negative impact of brachiaria on ant genres richness, which is perceptible by the greater richness of the samplings carried out in native grass, in relation to the lower richness observed in the brachiaria. Considering the ant genera, 5 genera differed between areas invaded or not. Ectatomma and Paratrechina tended to occur more in areas with brachiaria while Apterostigma, Forelius and Gnamptogenys tended to do not occur in areas with brachiaria, 22 genres were identified in this study. These results suggest a negative effect of the brachiaria on the richness of ant genres in the cerrado and an influence in certain genera of ants. A more refined taxonomic classification of ants (at the specific level) may allow further elucidation of the invasion effect. Thus, further steps should include the refinement of the taxonomic classification of the insects collected to allow reanalysis of the data at a specific level.
The impact of the invasion of brachiaria (Urochloa sp.) on the diversity of ants in the cerrado of the ecological station of Santa Bárbara and Itirapina, sp.
Keywords: Invasão biológica; Cerrado; Gramíneas invasoras; Biological invasion; Invasive grass; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS